Participa????o do estado e desempenho de projetos complexos de infraestrutura no agroneg??cio brasileiro - Steffen Neto, Frederico (2015)
The Brazilian agribusiness is one of the generators of wealth origins of Brazil, accumulating growth for decades, contributing significantly in the rate of gross domestic product (GDP), and placing the country among the nations that produce more agroindustrial commodities. The rapid growth of agribusiness has shown that the available infrastructure is insufficient for actual needs. Facing this situation presented this dissertation is meant to examine the state's participation in the performance of the infrastructure of complex projects in agribusiness. In face of this objective the research question that arises is: "How much the participation of the State interferes with the performance of infrastructure complex projects in agribusiness?" In order to answer it was developed 05 hypotheses and researches carried out in the works of literature concerning the theoretical axes defined as supporters of this research: Agribusiness Sector Complex and Performance Project, Participation and State Role in Infrastructure Projects Complexes in Agribusiness. The data used in this study were obtained through consultations in Annuals exemplary of Infrastructure of Exame magazine, covering the biennium 2014/2015 and specific sites related in some way with the theme of this work. The method used in this study is descriptive, quantitative, inferential method making use of multivariate data analysis technique. The results confirmed, the study framework, which the Brazilian government actively participates as a major stakeholder in the infrastructure of complex projects in agribusiness, with consequent impact on the performance of the same. The present study contributes to both the academia and the practice by presenting the impacts of state participation in infrastructure complex projects in agribusiness. The main practical contribution of this work was to present a quantitative way, through the data obtained and the technique used to analysis; multivariate data analysis, which can influence other factors, including external, in compliance with the objectives of these projects, in particular working in the state's participation in infrastructure projects in the agribusiness complex.